Meningkatkan pemahaman siswa sma melalui penggunaan peta konsep pada materi IPA - Azmi, Jihan; Salsabilla, Nisvie Nur; Yulyana, Puspa; Ambarwati, Upik; Slamet, Zahra Anindya Putri; Zaini, Muhammad; Rezeki, Amalia; Putra, Aminuddin Prahatama; Riza, Muhammad Faisal; Fajeriadi, Hery (Journal of Bio-Creaducation, 2025)
Concept maps are a very important visual tool in the learning process, serving to illustrate the relationship between concepts systematically. By using concept maps, students can understand and organize information better, thus improving their critical and creative thinking skills. Overall, an understanding of concept maps is essential in the modern educational context. Concept maps not only serve as learning aids, but also as a bridge to connect various complex ideas and concepts, thus facilitating more effective and efficient learning. This study aims to examine the effectiveness of using concept maps in improving students' understanding of science materials. This study was conducted based on the analysis of two classroom action researches (PTK) conducted by Amalia Rezeki and Muhammad Faisal Riza. The research shows that the use of concept maps as learning media is effective in improving student learning outcomes, both individually and classically. The research method used was descriptive with two cycles, including planning, implementation, observation, and reflection. Data were obtained through pretest, posttest, formative test, and student activity observation. The results showed a significant increase in student understanding, with individual learning completeness reaching ≥ 65 and classical completeness ≥ 85%. Students' learning activities became more active, such as making concept maps and group discussions. Concept maps proved to be able to connect new information with students' prior knowledge, resulting in meaningful learning. These findings support the importance of applying innovative learning methods such as concept maps to improve the quality of education.Peta konsep merupakan alat visual yang sangat penting dalam proses pembelajaran, berfungsi untuk menggambarkan hubungan antar konsep secara sistematis. Dengan menggunakan peta konsep, siswa dapat memahami dan mengorganisasikan informasi dengan lebih baik, sehingga meningkatkan kemampuan berpikir kritis dan kreatif mereka. Secara keseluruhan, pemahaman tentang peta konsep sangat penting dalam konteks pendidikan modern. Peta konsep tidak hanya berfungsi sebagai alat bantu belajar, tetapi juga sebagai jembatan untuk menghubungkan berbagai ide dan konsep yang kompleks, sehingga memfasilitasi pembelajaran yang lebih efektif dan efisien. Penelitian ini bertujuan untuk mengkaji efektivitas penggunaan peta konsep dalam meningkatkan pemahaman siswa pada materi IPA. Kajian ini dilakukan berdasarkan analisis dua penelitian tindakan kelas (PTK) yang dilaksanakan oleh Amalia Rezeki dan Muhammad Faisal Riza. Penelitian menunjukkan bahwa penggunaan peta konsep sebagai media pembelajaran efektif dalam meningkatkan hasil belajar siswa, baik secara individu maupun klasikal. Metode penelitian yang digunakan adalah deskriptif dengan dua siklus, mencakup perencanaan, pelaksanaan, observasi, dan refleksi. Data diperoleh melalui pretes, postes, tes formatif, dan observasi aktivitas siswa. Hasil penelitian menunjukkan peningkatan signifikan dalam pemahaman siswa, dengan ketuntasan belajar individu mencapai ≥ 65 dan ketuntasan klasikal ≥ 85%. Aktivitas belajar siswa menjadi lebih aktif, seperti membuat peta konsep dan berdiskusi kelompok. Peta konsep terbukti mampu menghubungkan informasi baru dengan pengetahuan awal siswa, sehingga menghasilkan pembelajaran yang bermakna. Temuan ini mendukung pentingnya penerapan metode pembelajaran inovatif seperti peta konsep untuk meningkatkan kualitas pendidikan.